Divergent perceptions from MOOC designers and Learners on Interaction and learning experience: findings from the Global MOOQ Survey - Teixeira, António (2018)
In this paper, we present the first results from the Global MOOC Quality Survey .The survey was developed for three target groups: learners, designers and facilitators of MOOCs. Final objective is the development of the Quality Reference Framework (QRF) with quality indicators and tools in close collaboration with all interested stakeholders worldwide.